2004
DOI: 10.1159/000077162
|View full text |Cite
|
Sign up to set email alerts
|

MRI with Diffusion Tensor Imaging Post-Mortem at 3.0 T in a Patient with Frontotemporal Dementia

Abstract: The formalin-fixed brain of a patient with clinically diagnosed frontotemporal dementia (FTD) was examined post-mortem using magnetic resonance imaging (MRI) with diffusion tensor imaging (DTI) at 3.0 T. Frontotemporal atrophy as well as bilateral frontal white matter abnormalities were seen. The white matter changes were slightly more extensive on DTI than on conventional MRI. Correlation with histopathology of the corresponding regions revealed typical frontal lobe degeneration of non-Alzheimer type, with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 10 publications
(12 reference statements)
2
41
0
1
Order By: Relevance
“…While further validation is needed, our results are consistent with those reported by Guo et al (2001), who found RA to be more sensitive than T 2 -weighted images in detecting dysmyelination in human Krabbe's disease and stem-cell transplantation. Similarly, Larsson et al (2004) found that DTI is relatively more sensitive than T 1 -or T 2 -weighted images in delineating myelin-related lesions.…”
Section: Dti Of Wt Shi and Transplanted Mice At Short T Diffmentioning
confidence: 88%
See 1 more Smart Citation
“…While further validation is needed, our results are consistent with those reported by Guo et al (2001), who found RA to be more sensitive than T 2 -weighted images in detecting dysmyelination in human Krabbe's disease and stem-cell transplantation. Similarly, Larsson et al (2004) found that DTI is relatively more sensitive than T 1 -or T 2 -weighted images in delineating myelin-related lesions.…”
Section: Dti Of Wt Shi and Transplanted Mice At Short T Diffmentioning
confidence: 88%
“…DTI has been used for detecting changes in myelination in the developing brain (Wimberger et al, 1995;Prayer et al, 1997;Neil et al, 1998) and in demyelinating diseases (Guo et al, 2001;Larsson et al, 2004), although its underlying contrast mechanism remains incompletely understood. There is some evidence that DTI is more sensitive for detecting demyelinating lesions relative to conventional T 1 -and T 2 -weighted imaging (Hajnal et al, 1991;Sukama et al, 1991;Wimberger et al, 1995;Prayer et al, 1997;Guo et al, 2001;Larsson et al, 2004). DTI contrast arises from barriers (such as cell membranes of axons and oligodendrocytes) that hinder water diffusion in some orientations more than others, giving rise to anisotropic diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…VCI provides a good model for assessing the clinical and research utility of quantitative DTI since ischemic white matter injury is associated with a characteristic pattern of increased diffusivity and decreased anisotropy (Jones et al, 1999). These diffusion changes are thought to reflect axonal loss (Beaulieu, 2002) with possible contributions from demyelination (Le Bihan et al, 2001), gliosis (Larsson, Englund, Sjobeck, Latt, & Brockstedt, 2004), or other pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Numerous postmortem DWI and DTI studies were performed in the animal and human brain; however, most evaluated the effect of formalin fixation and PMI on diffusion properties [18][19][20][21][22][23] or investigated isolated fixed human brains for the diagnosis of disease. 24,25 To date, there are only very few studies on DWI or DTI in the postmortem unfixed human brain in situ that have concentrated on general characteristic changes in postmortem MR imaging and CT, including DWI on one hand and postmortem DTI in a single case with a brain stem trauma on the other. 17,26 In this study, we aimed at the evaluation of a potential application of DWI and DTI and particularly ADC and FA in different regions of the postmortem brain in situ for the application in forensic diagnostics.…”
mentioning
confidence: 99%